Contributing factors to postoperative surgical site infections in pituitary neuroendocrine tumors undergoing endonasal transsphenoidal resection - Lei Wang; Shanxian Liu; Jie Zheng; Rui Li; Zhenyi Xing (Scientific Reports)
Abstract Pituitary Neuroendocrine Tumors (PitNETs), often treated via endonasal transsphenoidal resection, present a risk for postoperative surgical site infections (SSIs), including intracranial infections such as meningitis. Identifying the risk factors associated with these infections is crucial for improving surgical outcomes and patient care. A retrospective study was conducted at a medical center from June 2020 to June 2023. The study included 20 patients with postoperative intracranial infections and 50 controls without infections. Inclusion criteria involved adult patients diagnosed with PitNETs who underwent standard endonasal transsphenoidal surgery and provided informed consent. Exclusion criteria included previous neurosurgical procedures, preoperative infections, concurrent severe diseases, or alternative surgical approaches. Diagnostic criteria for intracranial infections were based on clinical, hematological, cerebrospinal fluid, radiological, and microbiological findings. Statistical analyses were performed using IBM SPSS, focusing on univariate and multivariate logistic regression analyses. Univariate analysis showed no significant association of intracranial infections with factors like smoking history, previous craniotomy, operation time, hypertension, preoperative sphenoid sinusitis, BMI, and age. However, postoperative CSF leaks, intracranial pneumocephalus, diabetes mellitus, and tumor extension to the third ventricle were significantly associated with infections. Multivariate logistic regression further confirmed these findings, with significant odds ratios for these factors. The study reveals a significant correlation between postoperative CSF leaks, intracranial pneumocephalus, diabetes mellitus, and tumor extension to the third ventricle with the occurrence of SSIs following endonasal transsphenoidal resection of PitNETs. Microbial analysis revealed Escherichia coli as the most prevalent pathogen in post-surgery infections, with notable antibiotic resistance patterns observed in key bacteria, necessitating careful antibiotic selection. Tailored clinical treatment strategies addressing these risk factors are essential to reduce the incidence of postoperative SSIs and enhance patient safety.